Content Controlled Image Representation for Sports Streaming - KOKARAM, ANIL; PITIE, FRANCOIS (Suvisoft, 2005)
Content based analysis has traditionally been posed in the context of identifying some material in response to a user query. This paper illustrates that given a content based analysis process that can identify semantic events in a sequence, that sequence can then be changed in various ways. A Motion Keyframe is presented to re-express the viewing of a sequence. The notion of content analysis for control of other media processing engines is introduced. Tennis footage is used to illustrate the ideas since sports in general contains strong contextual information.
IEEE workshop on Content Based Multimedia Indexing (CBMI'05)
PUBLISHED
Riga, Latvia
Keywords: Electronic & Electrical Engineering